Assessment of Multiplate platelet aggregometry using citrate, heparin or hirudin in Rhesus macaques. (17th November 2015) - Dugan, Greg; O'Donnell, Lisa; Hanbury, David B.; Cline, J. Mark; Caudell, David L.
Abstract: Electrical impedance aggregometry (EIA) has gained popularity in clinical and research applications. Nonhuman primates are used to study disease and drug-related mechanisms that affect hemostasis, therefore establishing normal EIA parameters are necessary. The anticoagulants sodium heparin, hirudin and sodium citrate and three agonists, ADP, ASPI, and collagen were evaluated. Whole blood from 12 adult male rhesus macaques was collected to evaluate anticoagulants, sodium heparin, hirudin and sodium citrate using three agonists (ADP, ASPI and collagen), on the Multiplate® 5.0 Analyzer. Platelet function was reported for three parameters: Area under the curve (AUC), aggregation, and aggregation velocity. There was a significant difference in mean AUC between citrate and heparin samples, and citrate and hirudin samples regardless of the agonist used. There was no difference in AUC between heparin and hirudin. ADP-activated samples showed an increase in impedance with hirudin samples compared to citrate. Furthermore, heparin and hirudin out-perform citrate as the anticoagulant for EIA in the macaque. Finally, this study demonstrates the utility of the Multiplate® system in this model and provides important insight into anticoagulant choice when using EIA.